Finding Consensus About the Level of Medication Safety in a Hospital Setting: Development and an Example of Application of a Modified Delphi Method - Böhmdorfer-McNair, Birgit; Huf, Wolfgang; Strametz, Reinhard; Nebosis, Michael; Pichler, Florian; Janowitz, Susanne Melitta; Ettl, Brigitte (Frontiers in Public Health, 2021)
A version of the ISMP (Institute for Safe Medication Practices) questionnaire adapted to the Austrian inpatient setting was used to sample the estimates of a group of experts regarding the level of medication safety in a level II hospital. To synthesize expert opinions on a group level reproducibly, classical Delphi method elements were combined with an item weight and performance weight decision maker. This newly developed information synthesis method was applied to the sample dataset to examine method applicability. Method descriptions and flow diagrams were generated. Applicability was then tested by creating the synthesis of individual questionnaires. An estimate for the level of medication safety in an Austrian level II hospital was thus generated. Over the last two decades, initiatives regarding patient safety in general and the medication safety in particular have been gaining momentum. Questionnaires are state-of-the-art to assess medication practice in healthcare facilities. Acquiring consistent data about medication in the complex setting of a hospital, however, has not been standardized. There are no publicly available benchmark datasets and, in particular, there is no published method to reliably synthesize expertise regarding medication safety on an expert group level. The group level information synthesis method developed has the potential to synthesize information about the level of medication safety in a hospital setting more reliably than unstructured approaches. A medication safety level estimate for a representative Austrian level II hospital was generated. Further studies are needed to establish convergence characteristics and benchmarks for medication safety on a larger scale.